B Cells in Autoimmune Diseases - Christiane S. Hampe (Scientifica)
The role of B cells in autoimmune diseases involves different cellular functions, including the well-established secretion of autoantibodies, autoantigen presentation and ensuing reciprocal interactions with T cells, secretion of inflammatory cytokines, and the generation of ectopic germinal centers. Through these mechanisms B cells are involved both in autoimmune diseases that are traditionally viewed as antibody mediated and also in autoimmune diseases that are commonly classified as T cell mediated. This new understanding of the role of B cells opened up novel therapeutic options for the treatment of autoimmune diseases. This paper includes an overview of the different functions of B cells in autoimmunity; the involvement of B cells in systemic lupus erythematosus, rheumatoid arthritis, and type 1 diabetes; and current B-cell-based therapeutic treatments. We conclude with a discussion of novel therapies aimed at the selective targeting of pathogenic B cells.